Epidemiological Study and Anatomical Involvement Pattern of Squamous Cell Carcinoma (SCC) of the Head and Neck in Western Iran (Kermanshah) during 2013-2021 - Javad Azimibaghar; Roya Chegenelorestani; Nazanin Moghaddasi Nia; Etrat Javadirad (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2023)
Introduction: Squamous cell carcinoma accounts for about 90% of head and neck cancers. The present study aimed to investigate the epidemiology and anatomical involvement pattern of squamous cell carcinoma (SCC) in the head and neck region from 2013-2021 in Imam Khomeini Hospital, Kermanshah, Iran. Material & Methods: This descriptive cross-sectional study was conducted on all the patients with SCC of the head and neck treated at Imam Khomeini Medical Center in Kermanshah over a period of 10 years. Demographic and pathological information was extracted from the patients' medical records. Then, the obtained data was analyzed in SPSS software (version 23). Findings: Out of 299 patients identified with SCC, 236 (78.9%) were male, and the remaining were female. The majority of the patients (48.8%) fell within the age group of 55-72 years, with 57.9% reporting a history of smoking and 76.9% residing in urban areas. Among those studied, the most commonly affected site was the larynx, accounting for 49.5% (148) of cases. The highest incidence of head and neck cancers in both men and women was observed in 2019, with 15.9% and 15.7% of cases, respectively. Discussion & Conclusion: The results of this study showed that most patients were older men over 50, who mostly lived in the city and smoked. The most anatomical site of involvement was the larynx. Therefore, it is recommended to pay attention to these risk factors to prevent and control these cancers.